Addressing consumer skepticism: effects of post-purchase green attribute disclosure on consumer attitude change - Yan Zhang; Qianyu Zhang; Xiaoyong Li (Humanities & Social Sciences Communications)
Abstract As environmental awareness grows, consumer responses to corporate sustainability claims vary widely, with some embracing green products and others remaining skeptical. Existing research primarily examines pre-purchase decision-making, leaving a gap in understanding how post-purchase revelations influence consumer attitudes. Drawing on behavioral reasoning theory, this study explores how post-purchase disclosure of core (e.g., eco-friendly fabrics) and peripheral (e.g., recycled packaging) green attributes influences consumer perceptions. Compared to peripheral attributes, core attributes are more likely to trigger perception that conflicts with pre-purchase beliefs. Through a scenario-based experimental design focused on green apparel, we find that post-purchase exposure to credible environmental information can mitigate initial skepticism, improving attitudes and encouraging brand advocacy. These effects depend on the centrality of the green attributes and are moderated by self-affirmation. Core green attributes may enhance risk perception, while self-affirmation helps consumers reconcile doubts, maintaining brand advocacy. These findings contribute to theoretical understandings of green skepticism, demonstrating its malleability, and offer practical insights for marketers. By strategically communicating green attributes post-purchase, firms can encourage hesitant buyers to support sustainability efforts.